Doxorubicin-Induced Cardiac Toxicity Is Mediated by Lowering of Peroxisome Proliferator-Activated Receptor δ Expression in Rats. (28th February 2013) - Chen, Zhih-Cherng; Chen, Li-Jen; Cheng, Juei-Tang
Abstract : The present study investigates the changes of peroxisome proliferator-activated receptors δ (PPAR δ ) expression and troponin phosphorylation in heart of rats which were treated with doxorubicin (DOX). Wistar rats which were treated with DOX according to a previous method. The protein levels of PPAR δ and troponin phosphorylation were measured using Western blot. The PPAR δ expression in heart was markedly reduced in DOX-treated rats showing a marked decrease in cardiac dP/dT and cardiac output. Also, cardiac troponin phosphorylation was lowered in DOX-treated rats. Meanwhile, combined treatment with the agonist of PPAR δ (GW0742) reversed the decrease of cardiac dP/dT and cardiac output in DOX-treated rats. Then, primary cultured cardiomyocytes from neonatal rats were used to measure the changes of calcium concentration in cells. In addition to both decrease of PPAR δ expression and troponin phosphorylation in neonatal cardiomyocytes by DOX, a marked decrease of calcium concentration was also observed. Our results suggest the mediation of cardiac PPAR δ in DOX-induced cardiotoxicity in rats. Thus, activation of PPAR δ may restore the expression of p-TnI and the cardiac performance in DOX-induced cardio toxicity in rats.